Low-cost seaweed biomass treatment with formaldehyde for cationic dyes removal from aqueous solutions - D. M. Polanco-Gamboa; Mohamed Abatal; D. M. Polanco-Gamboa; Claudia Aguilar; Francisco Anguebes-Fransechi; Eder C. Lima; Joel Vargas; Ismeli Alfonso; A Quiroz (Adsorption Science & Technology)
This paper aims to investigate the uptake of two basic dyes (methylene blue [MB] and brilliant cresyl blue [BCB]) using the formaldehyde-treated algae Fucus vesiculosus (FV-FORMALD). The surface and morphology of modified biomass was characterized by the point of zero-charge (pH PZC ), Brunauer–Emmett–Teller (BET) surface area ( S BET ), scanning electron microscopy (SEM/EDS), and Fourier-transform infrared spectroscopy. The equilibrium data were best described by the Langmuir and Freudnlich isotherm model for MB and BCB, respectively. Kinetics modeling shows that the adsorption of both dyes onto FV-FORMALD was well described by pseudo-second order. The thermodynamics parameters validated the exothermic nature and the spontaneously of the adsorption of both dyes. The optimum conditions for the adsorption of MB and BCB were at pH = 8 and 4, adsorbent concentration = 2 and 1 g L −1 , and T  = 313.15 and 300.15 K, respectively. The FV-FORMALD had reuse potential for at least three cycles with high adsorption capacities of MB and BCB dyes. A colored real wastewater was successfully treated using FV-FORMALD. According to the results, the brown algae FV-FORMALD could be considered appropriate for removing cationic dyes due to its high efficiency and an environmentally friendly, sustainable, and low-cost approach.